Epstein-Barr virus-positive inflammatory follicular dendritic cell sarcoma with significant granuloma: case report and literature review - Chenchen Nie; Xun Xie; Hangyan Li; Yangcan Li; Zhihong Chen; Yanchun Li; Zhenfeng Li (BMC, 2024)
Abstract Background Epstein-Barr virus-positive inflammatory follicular dendritic cell sarcoma (EBV+IFDCS) is a rare disease characterized by mild clinical symptoms and non-specific imaging findings. The diagnosis of the disease depends on pathological diagnosis. However, EBV+IFDCS has a very broad spectrum of histological morphology and immune phenotypes, and its histopathological features have not been fully described by pathologists. Case presentation A 59-year-old female, with no significant discomfort, was found to have a splenic mass during a routine physical examination. Microscopic examination at low magnification revealed numerous epithelioid granulomas, amidst which a substantial inflammatory response was observed. Interspersed among the dense inflammatory cells were spindle or oval-shaped cells, distributed sporadically with indistinct boundaries. Under high magnification, these spindle cells had subtle features: smooth and clear nuclear membranes, inconspicuous small nucleoli, and infrequent mitotic figures. Immunophenotypically, the spindle cells expressed CD21 and CD23, and Epstein-Barr encoding region (EBER) in situ hybridization yielded positive results. The inflammatory milieu predominantly consisted of T cells, with a minority of plasma cells expressing IgG4. The confluence of morphological and immunohistochemical findings led to the final pathological diagnosis of EBV+IFDCS in this case. Conclusions The presentation of EBV+IFDCS with pronounced granulomatous changes is rare. This morphological variant poses a high risk of misdiagnosis, frequently leading to confusion with other granulomatous diseases. Accurate diagnosis necessitates a comprehensive analysis, integrating immunohistochemistry and in situ hybridization. The case presented here is instrumental in raising awareness and understanding of EBV+IFDCS, with the goal of reducing misdiagnoses and unrecognized cases.